Operational Planning and Organizational Performance of the Federal Ministry of Education, Abuja, Nigeria - Ikupolati, Michael Sunday; Achumba, Dorathy Uduak; Shehu, Mohammed; Akpan, Ekanem Benedict (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
There is wrong application of operational planning, by the workers of the Federal Ministry of Education (FME), Abuja. In an attempt to address this unfortunate development, there is the need to critically investigate the importance of planning on organizational performance to enable management to appreciate its worth in gaining competitive advantage. This study examines the influence of operational planning on organizational performance in Nigeria Federal Ministry of Education. The research design employed in the study was the descriptive approach, where issues will be effectively analyzed through research questions, test hypotheses and establishment of relationships between the variables of interest. Scores generated from the research instrument with Statistical Package for Social Science (SPSS) version 27 and were analyzed using the weighted mean score and simple linear regression statistical technique. The study results indicated that operational planning had a positive and significant influence on the organizational performance of the federal ministry of education in Nigeria. It was also discovered that there exists a strong positive and significant relationship between operational planning and organizational performance at the federal Ministry of education, Abuja, which implies that an improvement in operational planning will lead to increase in organizational performance. The study suggests that investing in robust planning infrastructures, fostering a culture of continuous improvement, and leveraging technological advancements to streamline planning and execution processes will improve work performance in FME.